Mycobacterium tuberculosis infection in women with unexplained infertility - Maryam Eftekhar; Soheila Pourmasumi; Parvin Sabeti; Abbas Aflatoonian; Mohammad Hasan Sheikhha (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2015)
Background: Genital tuberculosis (GTB) is an important cause of female infertility, especially in developing countries. The positive results of polymerase chain reaction (PCR) in endometrial GTB in the absence of tubal damage raise the possibility of the detection of sub-clinical or latent disease, with doubtful benefits of treatment. Objective: To evaluate the mycobacterium tuberculosis infection in endometrial biopsy samples collected from unexplained infertile women attending Yazd Research and Clinical Center for Infertility by using PCR techniques. Materials and Methods: In this cross sectional study, 144 infertile women with unexplained infertility aged 20-35 years old and normal Histro-saplango graphy findings were enrolled. Endometrial biopsy samples from each participant were tested for mycobacterium tuberculosis detecting by PCR. In 93 patients, peritoneal fluid was also taken for culture and PCR. Results: The PCR results of endometrial specimens were negative in all cases, demonstrating that there was no GTB infection among our patients. Conclusion: Our results showed that GTB could not be considered as a major problem in women with unexplained infertility. Although, studies have indicated that PCR is a useful method in diagnosing early GTB disease in infertile women with no demonstrable evidence of tubal or endometrial involvement.